absalg22 - Arkansas Tech University MATH 4033: Elementary...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Arkansas Tech University MATH 4033: Elementary Modern Algebra Dr. Marcel B. Finan 22 Quotient Groups Lets look closely on the construction of the group (ZZ n , ) . We know that the elements in ZZ n are equivalence classes of the equivalence relation defined on ZZ by a b if and only if n | ( a- b ) . Also, an element of ZZ n is a right coset. Indeed, if 0 k < n then < n > + k = [ k ] = { nq + k : q ZZ } . The operation is defined by [ a ] [ b ] = [ a + b ] or using right cosets ( < n > + a ) ( < n > + b ) = < n > +( a + b ) . Note that the cyclic group < n > is a normal subgroup of ZZ since ZZ is Abelian (See Example 21.4). We are going to use the above ideas to construct new groups where G is a group replacing ZZ and N is a normal subgroup of G playing the role of < n > . More precisely, we have the following theorem. Theorem 22.1 Let N be a normal subgroup of a group G and let G/N be the set of all right cosets of N in G. Define the operation on G/N G/N by ( Na )( Nb ) = N ( ab ) . Then ( G/N, ) is a group, called the quotient group of G by N. Proof. is a well-defined operation We must show that if ( Na 1 ,Nb 1 ) = ( Na 2 ,Nb 2 ) then N ( a 1 b 1 ) = N ( a 2 b 2 ) . To see this, since ( Na 1 ,Nb 1 ) = ( Na 2 ,Nb 2 ) then Na 1 = Na 2 and Nb 1 = Nb 2 . Since a 1 = ea 1 Na 1 then a 1 Na 2 so that a 1 = na 2 for some n N. Sim- ilarly, b 1 = n b 2 for some n N. Therefore, a 1 b 1 = na 2 n b 2 . Since N / G then a 2 n a- 1 2 N, say a 2 n a- 1 2 = n 00 N. Hence, a 2 n = n 00 a 2 so that a 1 b 1 = nn 00 a 2 b 2 . But nn 00 N so that a 1 b 1 N ( a 2 b 2 ) . Since N ( a 2 b 2 ) is an equivalence class and a 1 b 1 N ( a 2 b 2 ) then N ( a 1 b 1 ) = N ( a 2 b 2 ) (Theorem 9.2). is associative Let a,b,c G. Then Na ( NbNc ) = Na ( Nbc ) = N ( a ( bc )) = N (( ab ) c ) = N ( ab ) Nc = ( NaNb )( Nc ) 1 where we used the fact that multiplication in G is associative....
View Full Document

This note was uploaded on 01/18/2012 for the course INFORMATIK 2011 taught by Professor Phanthuongcang during the Winter '11 term at Cornell University (Engineering School).

Page1 / 5

absalg22 - Arkansas Tech University MATH 4033: Elementary...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online